BAGI HASIL PERTANIAN DI DESA SUNGAI DERAS PERSPEKTIF TOKOH AGAMA TELUK PAKEDAI - Neisya Arrahmi; Abu Bakar; Nur Rahmiani (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
This research is motivated by the practice that occurs in Sungai Deras Village, there is anxiety related to the diversity of forms of borrowing and borrowing agricultural land which is indicated by differences in the distribution system and the amount. The purposes of this study are to determine: 1) the practice of sharing agricultural products that occurred in Sungai Deras Village; and 2) Teluk Pakedai religious leaders' views on sharing agricultural products in Sungai Deras Village. This study uses a qualitative method with the type of empirical research. Sources of data used primary data in the form of interviews with farmers, land owners and religious leaders while secondary data was in the form of books, journals, theses, and related articles that discussed agricultural production sharing practices and as reinforcement for data collection. Data collection techniques are interviews, observation and documentation. This data was analyzed by the descriptive analysis method, while the technical analysis of the data used by the researcher was data collection, data reduction, data presentation, and conclusion. Then, the data is checked for validity using time triangulation and member-check. The results of this study indicate that: 1) The practice of sharing agricultural land in Sungai Deras Village, Teluk Pakedai District, is by giving the land to farmers or cultivators with an agreement on sharing the results used in the community in muamalah called mukhabarah, muzara'ah and ijarah. 2) Religious leaders argue that they allow it because the agreement that occurs in the sharing of agricultural products is mutually beneficial for both the land owner and the cultivator. There is no coercion because both parties need each other.